A bathymetric compilation of the Cape Darnley region, East Antarctica. Issue 5 (October 2021) - Smith, Jodie; Nogi, Yoshifumi; Spinoccia, Michele; Dorschel, Boris; Leventer, Amy
Abstract: The Cape Darnley region in East Antarctica has been an area of scientific interest for a variety of disciplines over the last three decades. The recent acquisition of several high-resolution bathymetry datasets enabled the compilation of a detailed regional bathymetry grid. We present a high-resolution bathymetric compilation of the Cape Darnley region in East Antarctica, including areas of the Mac.Robertson Land shelf, slope and adjacent deep sea. A variety of data, single-beam and multibeam swath bathymetry and digitized depths from nautical charts were sourced from numerous institutions. The 100 m-resolution gridded bathymetric dataset improves previous bathymetric representations of the region and enables visualization of the seafloor morphology in unprecedented detail. The bathymetry grid has been constructed using a layered hierarchy approach based on the source of each dataset. This data compilation forms important baseline information for a range of scientific applications and end users including oceanographers, glacial modellers, biologists and geologists. The compilation will aid numerical modelling of ocean circulation, reconstruction of palaeo-ice streams and refinement of ice-sheet models.